2010
DOI: 10.1007/s00417-010-1576-6
|View full text |Cite
|
Sign up to set email alerts
|

No consequences of dietary n-3 polyunsaturated fatty acid deficiency on the severity of scopolamine-induced dry eye

Abstract: Our data suggest that an n-3 PUFA deficiency does not increase the severity of dry eye in a rat model of dry eye.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 28 publications
(37 reference statements)
0
13
0
Order By: Relevance
“…IgA) (Sullivan et al, 1993). Animal models have also demonstrated that dietary fatty acids can be incorporated in lacrimal gland tissue (Schnebelen et al, 2009;Viau et al, 2011) and that a diet rich in omega-3 fatty acids may be protective for some forms of dry eye ). Striking differences exist, however, between the human and animal tear lipidome, making many animals unsuitable as an animal model of ocular surface homeostasis (Butovich et al, 2012(Butovich et al, , 2008.…”
Section: Malnutrition Omega Fatty Acids Sjögren's Syndromementioning
confidence: 96%
“…IgA) (Sullivan et al, 1993). Animal models have also demonstrated that dietary fatty acids can be incorporated in lacrimal gland tissue (Schnebelen et al, 2009;Viau et al, 2011) and that a diet rich in omega-3 fatty acids may be protective for some forms of dry eye ). Striking differences exist, however, between the human and animal tear lipidome, making many animals unsuitable as an animal model of ocular surface homeostasis (Butovich et al, 2012(Butovich et al, , 2008.…”
Section: Malnutrition Omega Fatty Acids Sjögren's Syndromementioning
confidence: 96%
“…IFN-γ has been proposed as a biomarker for dry eye disease and Sjögren syndrome (SS) because elevated IFN-γ, either protein and/or RNA, has been detected in tears, saliva, conjunctiva, submandibular glands and blood [tears (Boehm et al, 2011; Corrales et al, 2007; de Paiva et al, 2007a; Enriquez-de-Salamanca et al, 2010; Lam et al, 2008; Massingale et al, 2009; Mrugacz et al, 2006; Riemens et al, 2012), conjunctiva (Chen et al, 2011; Chen et al, 2006; Corrales et al, 2007; de Paiva et al, 2007a; Zhang et al, 2011b) , saliva (Kang et al, 2011; Pertovaara et al, 2006), lacrimal (de Paiva et al, 2010a; Hayashi et al, 2012; Jie et al, 2010; Ogawa et al, 2002; Pelegrino et al, 2012; Rahimy et al, 2010b; Viau et al, 2011) submandibular glands (Brookes et al, 1995; Hayashi et al, 2012; Koarada et al, 2006; Kohashi et al, 2008; Mrugacz et al, 2006), and blood (Hagiwara et al, 1998; Szodoray et al, 2008)] Evidence from mouse models and human SS patients indicate that IFN-γ is a relevant therapeutic target (de Paiva et al, 2007; de Paiva et al, 2011; Ogawa et al, 2002). …”
Section: 1 Th1 Pathwaymentioning
confidence: 99%
“…IFN-γ expression has been evaluated in minor salivary glands of human SS patients, as well as lacrimal and submandibular (SMG) gland biopsies in animal models. Virtually every mouse autoimmune model that mimics SS, or even environmentally-induced mouse dry eye models have shown increased expression of IFN-γ in submandibular and/or lacrimal glands (de Paiva et al, 2010a; Hayashi et al, 2012; Jie et al, 2010; Kohashi et al, 2008; Mitsias et al, 2002; Ogawa et al, 2002; Pelegrino et al, 2012; Rahimy et al, 2010b; Viau et al, 2011). In cultured labial salivary gland biopsies obtained from SS patients, the concentration of IFN-γ, but not IL-13, was associated with greater lymphocytic infiltration (Mitsias et al, 2002).…”
Section: 1 Th1 Pathwaymentioning
confidence: 99%
“…This was already shown in several tissues including the retina 99 and lacrimal glands, 93 but also in tears. Reprinted from Viau et al (2011), 84 with permission. This means that the FIGURE 18.5 Expression of cytokines in the exorbital lacrimal glands of rats fed with the balanced diet or the n-3 polyunsaturated fatty acids (PUFA)-deficient diet for three generations and treated or not with continuous scopolamine (12.5 mg/day) for 10 days.…”
Section: N-3 Polyunsaturated Fatty Acids Supplementation and Dry Eyementioning
confidence: 99%
“…Reprinted from Viau et al (2011), 84 with permission. The n-3 PUFA-deficient diet did not increase the levels of the proinflammatory cytokine transcripts as compared to the balanced diet in control animals.…”
Section: Figure 186mentioning
confidence: 99%